Incidence of reproductive disorders in the stray dogs in Dehradun district of Uttaranchal - KUMAR, SARVESH; SHARMA, V K; SINGH, BEERENDRA (The Indian Journal of Animal Reproduction, 2007)
The study was conducted on 918 stray dogs in Dehradun brought for sterilization, 38 (4.14%)dogs were suffering with pathological conditions. The pathological conditions most encountered werevenereal tumor, 2.28% (2.36% female and 2.0% male) respectively, mammary tumor ( 1.11 % ), pyometra(0.97%) and unilateral cryptorchidism (1.0%).
Keywords: Stray dogs; Mammary tumor; Pyometra; Venereal tumor; Cryptorchidism